Relações e tensões em campo: tipificações e cultura vivida na série especial do Jornal Nacional com os jogadores da seleção brasileira - Steffen, Lauren Santos (2016)
This research discusses the tensions and relations between the typifications of soccer players, built by the special series with the Brazilian national team players on Jornal Nacional, and the elements present in the lived culture, from the political, economic and social context. The concept of lived culture will be based on the concept of practical consciousness developed by Williams (1979), that relates to what is actually being experienced, or the social experiences being defined and actively experienced by subjects in a given context. The aim of this study is to analyze the typifications built by the special series, in contrast with the elements of the lived culture. As specific objectives, this research aims: to study the typifications of soccer players in the sports television journalism; understand the relations between soccer and the political and economic developments of Brazil; check reinforced and silenced themes in the representations of sports television journalism and map the elements of the lived culture, from the political, economic and social context, present during the display of the special series on the TV news. For this, by drawing up a proposal for cultural-media analysis of the sports television journalism, from the perspective of the Cultural Studies, we developed an own diagram to observe our object through dynamic and interdependent spheres: the economy, the politics, the society and the sports television journalism, all inserted in the social environment as material practices. To map the typifications built in Maxwell's, Victor‟s and Daniel Alves‟ life stories in the series, we use the methodology of textual analysis (CASETTI; CHIO, 1999), from the use of the categories of a) subjects and interactions and b) history. Through the analysis, we came to three typifications of the soccer players represented in the series: the poor type, characterized as hegemonic and representative of most of these athletes, which is highlighted in the series; the graduated type, represented in the series only by the case of the player Victor, for whom is made a concession in the series, and finally, the rich type, represented by the single example of the player Maxwell in the series, which is represented by an attenuated form. The graduated and the rich types, since they are rare cases in the sport, are regarded as counter-hegemonic representations because they challenge the narrative pattern of such life stories. In seeking to highlight the role of the soccer players, placing them as main characters, the TV channel and the TV news comply only with a marketing task, trying to gain audience and generate identification through an illusory and homogeneous representation. On the other hand, this false role covers many problematic situations, conveying the idea that the soccer players are valued and represented in the series, without taking into account the diversity and the plurality of their life stories. Thus, the series does not put at issue new representations that could lead to different identity constructions of the soccer player in Brazil.